2011
DOI: 10.3233/jad-2011-110740
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment: Prodromal Alzheimer's Disease or Something Else?

Abstract: The majority of mild cognitive impairment (MCI) studies use baseline and one follow-up measurement to determine the clinical course of the disorder. This report of MCI clinical course is based on the a statistical evaluation of multiple neurocognitive tests over a 60 month period in elderly normal and MCI cohorts. The data includes serial informant-based measures (Clinical Dementia Rating [CDR]) and a comprehensive battery of neuropsychological tests analyzed by two different regression methods. Twenty-nine el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
1
13
0
4
Order By: Relevance
“…But when practice effects have been observed in MCI, they were most robust on memory measures (Duff et al, 2007; Machulda et al, 2013; Yan & Dick, 2006). The absence of practice effects on the processing speed tests would also be supportive of existing studies that have failed to find improvements in patients with MCI (Britt et al, 2011; Cooper et al, 2004; Darby et al, 2002; Schrijnemaekers et al, 2006). These seemingly discrepant findings might be expected given the meta-analysis of Calamia et al (2012), who noted that practice effects vary depending on multiple factors, including the types of cognitive domains and tests examined.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…But when practice effects have been observed in MCI, they were most robust on memory measures (Duff et al, 2007; Machulda et al, 2013; Yan & Dick, 2006). The absence of practice effects on the processing speed tests would also be supportive of existing studies that have failed to find improvements in patients with MCI (Britt et al, 2011; Cooper et al, 2004; Darby et al, 2002; Schrijnemaekers et al, 2006). These seemingly discrepant findings might be expected given the meta-analysis of Calamia et al (2012), who noted that practice effects vary depending on multiple factors, including the types of cognitive domains and tests examined.…”
Section: Discussionsupporting
confidence: 67%
“…Perhaps not surprisingly, findings of practice effects in patients with mild cognitive impairment (MCI) have been equivocal. For example, some studies have reported an absence of practice effects in MCI on various cognitive measures across various retest intervals (Britt et al, 2011; Cooper, Lacritz, Weiner, Rosenberg, & Cullum, 2004; Darby, Maruff, Collie, & McStephen, 2002; Schrijnemaekers, de Jager, Hogervorst, & Budge, 2006). Conversely, others have reported improvements on repeated testing in these patients (Duff et al, 2007; Mathews et al, 2014; Yan & Dick, 2006), and that patients with MCI who do not show practice effects tend to have worse outcomes than those that do show improvements on retesting (Duff et al, 2011; Hassenstab et al, 2015; Machulda et al, 2013).…”
mentioning
confidence: 99%
“…Subjects were enrolled in the study from a community-based recruitment as previously reported [9, 10]. Briefly, individuals with subjective memory complaints were screened and those classified as MCI or early AD were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in a study with a serial testing strategy, Britt et al . () observed that 12.4% of the multiple domain MCI patients in their sample reverted to normal cognitive functioning. This proportion is similar to that obtained by Forlenza et al .…”
Section: Introductionmentioning
confidence: 95%
“…In comparison, the proportion of transitions to normal cognitive function is lower in multi-domain MCI. Thus, in a study with a serial testing strategy, Britt et al (2011) observed that 12.4% of the multiple domain MCI patients in their sample reverted to normal cognitive functioning. This proportion is similar to that obtained by Forlenza et al (2009) for a multiple domain MCI group (15%).…”
Section: Introductionmentioning
confidence: 99%